汉麻仁抗血栓活性肽的制备工艺优化 "Preparation process optimization of hemp kernel antithrombotic active peptide" - 石杰，张正海，魏连会，杨庆丽，李国巍，董艳，姬妍茹 "SHI Jie, ZHANG Zhenghai, WEI Lianhui, YANG Qingli, LI Guowei, DONG Yan, JI Yanru" (Zhongguo youzhi)
为获得具有抗血栓活性的汉麻仁多肽，以汉麻仁蛋白粉为原料，对其进行酶解得到汉麻仁抗血栓活性肽，并通过超滤纯化。通过单因素试验和响应面试验优化酶解工艺，并对纯化的汉麻仁抗血栓活性肽的分子质量分布进行测定。结果表明：汉麻仁蛋白粉酶解制备汉麻仁抗血栓活性肽的最佳工艺条件为采用胰蛋白酶、酶解温度40 ℃、料液比1∶ 25、酶添加量5.68%、pH 8.0，在此条件下酶解5 h凝血酶抑制率为84.70%；分子质量在3 000 Da以下的汉麻仁抗血栓活性肽在质量浓度为0.01 g/mL时有更高的凝血酶抑制率，可以达到99.38%；分子质量在3 000 Da以下的汉麻仁抗血栓活性肽中近70%分子质量为500~1 500 Da。综上，该方法制备并纯化得到的汉麻仁抗血栓活性肽具有高凝血酶抑制活性。 In order to obtain hemp kernel polypeptide with antithrombotic activity, hemp kernel protein powder was used as raw material to obtain hemp kernel antithrombotic active peptide by enzymatic hydrolysis, and it was purified by ultrafiltration. The enzymatic hydrolysis process was optimized by single factor experiment and response surface methodology, and the molecular weight distribution of hemp kernel antithrombotic active peptide purified were identified. The results showed that the optimal conditions for the enzymatic hydrolysis process were obtained as follows: using trypsin, enzymatic hydrolysis temperature 40 ℃, solid-liquid ratio 1∶ 25, enzyme dosage 5.68%, and pH 8.0. Under these conditions, the thrombin inhibition rate was 84.70% when the enzymatic hydrolysis time was 5 h. The hemp kernel antithrombotic active peptide with a molecular weight below 3 000 Da had a stronger thrombin inhibition rate at a mass concentration of 0.01 g/mL, which could reach 99.38%. Nearly 70% of the peptides with a molecular weight below 3 000 Da were peptides with a molecular weight of 500-1 500 Da. In summary, the hemp kernel antithrombotic active peptide prepared and purified by this method has high thrombin inhibitory activity.